Transisi kelembagaan dan isi siaran radio PEMDA menjadi radio publik lokal di Jawa Timur - Surokim Surokim; Tatag Handaka (Masyarakat, Kebudayaan dan Politik, 2014)
The existence of Local Government Radio (namely Radio Khusus Pemerintah Daerah, abbreviated as RKPD) in East Java Province, Indonesia faced many problems in post implementing of Broadcasting Act No. 32/2002. This study used constructivism paradigm. The method used in this research is descriptive research with qualitative analysis. This research conducted observation, indepth interview, limited discussion to collect data; complemented with secondary data. The research uses purposive sampling technique. The data analyzed along with data interpretation and narrative report writing. By the research, it is found that RKPD faced complex problems regarding transition of both institutions and broadcasting content programs. Until recent time, RKPD did not have a standard design to be a public radio, both in the institutional aspect and broadcasting content program. In fact, there were various types of institution and legal entities as result of interpreting the act. The Broadcasting content program was also still dominated by the government interest. The program also discussed public issues minimally and gave limited access for the public to participate and engage. Institutional design and broadcasting program should be designed according to act No. 32/2002 as public radio that reflected the interests of public and supporting of public service